Concept for developing a regional program on laboratory biosafety in health care institutions of Dnipropetrovsk region (Environment & Health, 2025)
The aim. To create a Concept for developing a regional program on laboratory biosafety in medical laboratories of health care facilities in Dnipropetrovsk region in accordance with the requirements of international standards.Materials and methods. Data collection was carried out through study visits to medical laboratories of healthcare institutions in the Dnipropetrovsk region, as well as through the analysis of checklists that were developed and provided to laboratories for completion. Gaps were identified using a gap-analysis and based on the requirements of international standards. This became the basis for the formation of the Concept and development of an educational program on laboratory biosafety.Results and discussion. The analysis of 45 checklists and results of 10 visits revealed gaps related to the lack of safe laboratory equipment in medical laboratories, the state of technical services in healthcare facilities, the insufficient level of knowledge on biosafety and biosecurity among laboratory personnel, and general organizational issues. Due to the lack of a well–established system of laboratory biosafety training in Ukraine, the cooperation with Oles Honchar Dnipro National University to develop the discipline “Biosafety and Biosecurity in Medical Laboratories” was started. Taking into account the results of cooperation with the university and based on current international standards and guidelines, the Concept for the Development of a Regional Laboratory Biosafety Program in Healthcare Facilities in the Dnipropetrovsk region was formed. The Concept is proposed as a biosafety and biosecurity guideline that will help to form a unified approach in the field of laboratory biosafety.Conclusions. The Concept is a pilot project and can serve as a model for the establishment of a national laboratory biosafety program. This will be an important step in meeting the requirements of international standards for the management of medical laboratories resources and processes for their successful accreditation. The Сoncept can also be applied in the future in different sectors and laboratory networks that are part of the National Laboratory Healthcare System of Ukraine within the framework of the “One Health” concept.
Keywords: biosafety; medical laboratories; personnel bioprotection; concept; educational program